Fruit analysis (Springer-Verlag, 1995)
The book describes in detail the latest quality control techniques of fruits like grapes, agrumen, peaches, persimmons, apricots, and nuts like almonds and chestnut. The classical stock of routine methods is extended to include most recent techniques, such as random amplified polymorphic DNA analysis (RAPD) for the genetic characterization of chestnut varieties